Os processos de expansão territorial urbana e suas consequências socioambientais no município de Cotia - SP - Pereira, Jeferson da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The socio-environmental problems that exist in the Brazilian cities, on its great majority, are due to the intense process of expansion of the use of the urban territory, after the second half of the century XX. Inadequate urban and environmental planning, as well as the palliative policies employed by public bodies and agencies to contain effects caused by past administrations, encountered immense challenges when it comes to environmental issues. The municipality of Cotia-SP, located in the metropolitan region of São Paulo, is a typical example of this situation. In order to understand the present situation, the dynamic and intense transformation of landscape aspects makes it necessary to understand the historical principles of occupation and land use and the economic activities that developed there. In fact, the central focus presented in this monography, sought to investigate the process that is most consistent with the current transformation that is urban territorial expansion. In this way, it‟s possible to identify the other activities of land use and occupation. In order to do so, as a case study, a territorial portion of the municipality was used as an analysis, and then to consider whether the planning policies adopted by local public authorities are part of a regional strategy. Above all, to rate whether the planning measures being applied are adequate and take into account the socio-environmental characteristics of the area, or only aim at meeting the economic interests of small groups with a certain privilege, and may even result in irreversible damage to society in general and impacting the environment

Os problemas socioambientais existentes nas cidades brasileiras, em sua grande maioria, são decorrentes do intenso processo de ampliação do uso do território urbano, após a segunda metade do século XX. O planejamento urbano e ambiental inadequado, assim como as politicas paliativas empregadas por órgãos e gestores públicos para conter efeitos causados por administrações passadas, deparou-se com imensos desafios quando referentes à questões relacionadas ao meio ambiente. O município de Cotia-SP, situado na região Metropolitana de São Paulo, é exemplo típico desta situação. Para entender o quadro atual de tal situação, a dinâmica e intensa transformação das feições da paisagem, se faz necessário entender os aspectos históricos da ocupação e uso solo e das atividades econômicas que ali se desenvolveram. De fato, o foco central apresentado neste trabalho de monografia, buscou pesquisar o processo que condiz mais com a transformação atual, ou seja, a expansão territorial urbana. Desta forma, cabe identificar as outras atividades de uso e ocupação do solo. Para tanto, como estudo de caso, utilizou-se como recorte de análise, uma porção territorial do município, e buscou-se ponderar a partir de então, se as politicas de planejamento adotadas pelo poder público local fazem parte de uma estratégia regional. Sobretudo, avaliar se as medidas de planejamento que estão sendo aplicadas estão adequadas e contemplam as características socioambientais da área, ou apenas visam atender interesses econômicos de pequenos grupos com certos privilégios, podendo inclusive resultar em danos irreversíveis à sociedade em âmbito geral e impactando ao meio ambiente
Keywords: Solo - Uso; Urbanização - Cotia (SP); Planejamento urbano - Cotia (SP); Bacias hidrograficas - Cotia (SP); Geografia ambiental; Geografia urbana; Geography